2011 International Workshop on Requirements Engineering for Electronic Voting Systems 2011
DOI: 10.1109/revote.2011.6045914
|View full text |Cite
|
Sign up to set email alerts
|

Side-channels and eVoting machine security: Identifying vulnerabilities and defining requirements

Abstract: Abstract-Election systems making use of eVoting machines are becoming more prevalent. However, security issues do exist within current products and proposed systems. One of these issues is the occurrence of implementation-specific information leakage, otherwise known as side-channel leakage. These have serious implications for voter secrecy. An attack based on electromagnetic leakage from Nedap voting machines has demonstrated that this type of leakage is a relevant issue within eVoting. Therefore, in this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, the proposed structures should be carefully examined. Although homomorphic encryption is generally agreed to be secure, for example, in the scheme proposed by Li et al [12] and analysis conducted by Wang et al and Qu et al, weaknesses were also identified [21][22][23]. Fontaine and Galand [24] argue that in general the proposed schemes are not very suitable for every use and their properties should be carefully studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proposed structures should be carefully examined. Although homomorphic encryption is generally agreed to be secure, for example, in the scheme proposed by Li et al [12] and analysis conducted by Wang et al and Qu et al, weaknesses were also identified [21][22][23]. Fontaine and Galand [24] argue that in general the proposed schemes are not very suitable for every use and their properties should be carefully studied.…”
Section: Introductionmentioning
confidence: 99%